The Relationship Between Fetal macrosomia Malpotition and with Premature Rupture of Membrane (PROM) at Hospital Dr. H. Moch. Ansari Saleh Banjarmasin - Dini Akbari Husna; Adriana palimbo; Nuraini Maulinda Nuraini Maulinda (Universitas Sari Mulia, 2018)
Objective: to identifying relationship of fetal macrosomia malpotition and with premature rupture of membranes at Hospital Dr. H. Moch. Ansari Saleh Banjarmasin.method:This research used a case control approach. The population consists of all delivery mothers at Hospital Dr. H. Moch. Ansari Saleh Banjarmasin in 2016. The sample is 148 delivery mothers. The Data was taken from medical records and Analyzed using Chi-Square at Î± = 0.05.Result:The result of the research shows that there is a correlation between fetal malpotition with PROM incidence p = 0.004, and there is significant relation between macrosomia with PROM incidence p = 0.028. Among These two variables, macrosomia is the variable that had the most significant relationship with PROM incidence. The values of OR is = 4.985. It means macrosomia 4,985 times more at risk of PROM than Reviews those who did not experience PROM.Conclusion:There is a relationship between fetal macrosomia malpotition and with premature rupture of membranes. routine antenatal care is expected to Prevent the incidence of KPDÂ Keys Word: fetal malpotition, macrosomia, premature rupture of membranes, delivery mother